Fiscal adjustment policies and fiscal deficit: the case of Tanzania - Kihaule, Arnold Mathias (Curtin University, 2006)
In Tanzania, fiscal adjustment policies emphasized an increase in tax revenue and cuts in public spending to correct the fiscal deficit. However, adjustment policies restricted the impact of fiscal policies in correcting fiscal deficit because they led to a low GDP growth and narrowed the tax base. The government overlooked the need to have an alternative tax base that could compensate for the fall in GDP growth. In that respect, the main purpose of this study is to examine the impact of fiscal adjustment policies in correcting the fiscal deficit in Tanzania in different adjustment periods in the 1973-2000 period. The thesis adopts a country study approach to analyse the effect of changes in the tax structure on the fiscal position using the primary balance as a proxy. The study also uses time series econometric methods to examine the impact of economic policy regime changes on public spending and GDP growth and the implications for fiscal policy in Tanzania. The study finds that changes in macroeconomic conditions either temporarily expanded or narrowed the tax bases and influenced the correction of the fiscal deficit in different years. Fiscal adjustment policies were pro-cyclical, thus leading to low GDP growth. This limited the effect of changes in the tax structure in reducing the fiscal deficit. Lastly, policy regime changes led to public spending instability and a structural break in the GDP data series. This signified that economic policy reforms caused fundamental changes in the economy, with implications for macroeconomic and fiscal policies in Tanzania. In sum, the results suggest that pro-cyclical policies are harmful for countries pursuing fiscal adjustment policies to correct a fiscal deficit.